Social media influence for repetitive behavior among Malaysian millennial blood donors - Azanin, Ahmad (2020)
This basic research aims to discover how persuasive advertisements via social media are perceived in maintaining blood donation behaviour among Malaysian Millennials. Inspiration for this study stems from inadequate discussion built in the Elaboration Likelihood Model corpus knowledge. Inconsistent empirical evidence on the motivation factor has drawn the research attention to fill the knowledge gap. Additionally, infancy knowledge on message content lures this study to further clarify message indices. Furthermore, inconclusive knowledge of social media effectiveness needs immediate clarification from this study. Anchored by the interpretivist paradigm, this qualitative study provides new knowledge through descriptive phenomenology. Trustworthiness protocol was executed to establish the quality principles. Multiple sources of data included in-depth interviews, field notes, and photo analysis deployed for triangulation basis. Purposive sampling was conducted, whereby the criteria used to select the sample are blood donors (i) with a minimum of two donations, and (ii) Malaysian Millennials. Data collected from four informants through in-depth interviews were manually transcribed and analysed. For validation, 57 advertisements from official Facebook and Instagram were analysed through thematic and content analysis. In essence, inductive reasoning was used to navigate the research direction. As a result, this study extended the domain of the Elaboration Likelihood Model to repetitive behaviour from the existing attitude domain. A specific taxonomy of motivation factors for repeat blood donors was successfully developed based on reallife experiences. Five elements of the message content were well clarified regarding reminder, campaign, information, and awareness and persuasive. Nevertheless, this study has expanded the understanding of the effectiveness of social media in promoting Millennial blood donations behaviour. Last but not least, this study has enhanced the explanation power of the Elaboration Likelihood Model in the social media context. Finally, this inter-disciplinary study has linked marketing and haematology knowledge in providing a remedy of blood donation issue for social wellbeing.